ELLAGITANNINS AND FLAVONOIDS FROM CUPHEA CARTHAGENENSIS (JACQ.) J.F.MACBR. ISOLATED BY SEMIPREPARATIVE LIQUID CHROMATOGRAPHY - Collantes Díaz, Ingrit Elida (2024)
Cuphea carthagenensis was selected by the Brazilian Ministry of Health (CEME Program 1984-1998) as a native source to develop phytomedicines for the public health service. The present work reports the isolation and identification of major ellagitannins and flavonoids present in the butanolic phase of the aqueous extract of the aerial parts of C. carthagenensis by semi-preparative High Perfomance Liquid Chromatography. The identification of the compounds was carried out by analysis of nuclear magnetic resonance spectrum and mass spectrometry. The well-defined ellagitannins were oenotein B (1), woodfordin C (3) and flavonoids were quercetin (8), and quercetin-3-O-β-D-glucuronopyranosideo (10). The ellagitannin trimer oenotein A (2) was also identified, but it is found in its possible anomeric mixtures, as well as a tetramer (4, 5, 6 and 7) also in its possible anomeric mixtures, the latter confirmed by the analysis of its mass spectra.